Western Education and Elite Nationalism in Nigeria 1882-1929 - Ahmed Bouchemal (Pr. Afkir Mohammed, 2017)
The present study will try to examine how Western education in Nigeria, as part of British officials program to govern and administer colonies, led to the emergence of an early elite nationalism between 1882 and 1929. It was a protest against the economic, social and cultural foundations of British colonialism and an attempt to re-establish Nigerian presence in politics, economics and culture. By 1842, the former indigenous education was largely replaced by the introduction of formal education of the Christian missions. These Christian missions established Christianity and introduced a Western mode of education. In such circumstances, the community of Western educated elite spawned by Christian teaching had asserted their rejection and frustration to the new religion as it was inadequate to their aspirations and ambitions. In 1882, however, British officials had assumed responsibility over all educational matters. The expectation was that these schools would produce a group of English educated elite ready to be recruited in the administrative cadre and became agents of trust and reliability. However, the ultimate outcome was the production of a Western educated elite greatly motivated to challenge British economic, social and cultural presence. By virtue of their education, English as a common language and a self-conscious African identity, the elite undertook action to promote the culture, language, economic development and political presence of their people. In the late 19th century, they denied Africans’ inferiority and defended the distinctiveness of African culture and African personality. In the 20th century, as the idea of a Pan-African unity was rejected, the elite saw to join the National Congress of British West Africa to develop a Pan-West African identity as a motto for their protests. By 1929, the elite had arrived at a clearly defined Nigerian national identity. This study lays the groundwork for examining the context in which the elite moved to shape their discourse of a Nigerian nationhood.